Viewing Landscapes Is More Stimulating Than Scrambled Images After a Stressor: A Cross-disciplinary Approach - Law, Mikaela; Minissale, Gregory; Lambert, Anthony; Nater, Urs M.; Skoluda, Nadine; Ryckman, Nathan; Tahara-Eckl, Lenore; Bandzo, Martina; Broadbent, Elizabeth (Frontiers in Psychology, 2020)
Research has demonstrated that nature is beneficial for many aspects of one’s health. This pilot study aimed to investigate whether viewing landscape artworks, as a form of representational nature, could improve psychological and physiological recovery from a laboratory stressor. A sample of 30 participants were randomised to one of two conditions: landscape and scrambled. After a laboratory stress task, participants in the landscape condition viewed a series of landscape paintings for 30 minutes; participants in the scrambled condition viewed digitally scrambled versions of these artworks as a control condition. Pupil size was measured while viewing the images using an eye-tracker. Affect, drowsiness and fatigue, and the salivary stress biomarkers, cortisol and alpha-amylase, were measured at baseline, after the stressor and after the artwork viewing period. After the viewing period, the scrambled condition had increased reports of low negative affect (which contains the variables of sleepy, dull and sluggish) (p=.045, ηp2=.12) and increased reports of drowsiness (p=.038, ηp2=.12). Salivary cortisol levels decreased more rapidly while viewing the scrambled images compared to the landscape artworks (p=.027, ηp2=.62). Lastly, pupil size while viewing the landscape artworks was larger than when viewing a blank screen (p=.025, ηp2=.33), an effect not seen in the scrambled condition. This pilot study suggests that viewing landscape artworks was more stimulating and reduced drowsiness after stress when compared to viewing scrambled images.